Case Report: Partial Response Following Nivolumab Plus Docetaxel in a Patient With EGFR Exon 20 Deletion/Insertion (p.N771delinsGF) Mutant Lung Adenocarcinoma Transdifferentiated From Squamous Cell Carcinoma - Zhu, Lingling; Liu, Yanyang; Gao, Honglin; Liu, Jiewei; Zhou, Qinghua; Luo, Feng (Frontiers in Cell and Developmental Biology, 2022)
The histological transformation from lung squamous cell carcinoma (LUSC) to lung adenocarcinoma (LUAD) and p. N771delinsGF mutations in EGFR exon 20 (ex20) are exceedingly rare in non–small cell lung carcinoma (NSCLC). EGFR ex20 mutations are insensitive to EGFR tyrosine kinase inhibitors in NSCLC. Here, we present a 76-year-old male smoker harboring LUAD with a novel p. N771delinsGF deletion/insertion mutation in EGFR ex20 transdifferentiating from advanced LUSC after chemoradiotherapy. The patient presented reduced hydrothorax and relieved tightness with the treatment of nivolumab plus docetaxel and carboplatin after the failure of second-line chemotherapy. The case highlights the importance of rebiopsy and molecular retesting after the progression of lung cancer and supports the idea that the combination of immune checkpoint blockade and chemotherapy may be an attractive option for patients with EGFR ex20 mutations associated with LUSC–LUAD transformation.